A Survey on knowledge attitude and practice of interns regarding nutrition in Kerman Medical University - Hossein Safizadeh; Maryam Azimi (Kerman University of Medical Sciences, 2005)
Background : Inappropriate nutrition has an important role in many pathological conditions including such common diseases as diabetes cancer and cardiovascular diseases Despite the recognition that physicians are often called upon to provide counseling in nutritional aspects of diseases nutrition does not hold the place it deserves in medical schools curricula especially in clinical and casebased teaching Objectve: The aim of this study was to determine the knowledge attitude and practice of interns in Kerman Medical University regarding the nutrition Methods: Selfadministered questionnaires including 29 questions and in a crosssectional study were completed by 105 interns Results: The mean knowledge attitude and practice scores were 693 ± 189 (out of 14) 1550 ± 354 (out of 40) and 148 ± 158 (out of 7) respectively There were no significant differences in knowledge and practice scores between males and females but male interns had higher score in attitude (P